2015
DOI: 10.1111/1754-9485.12338
|View full text |Cite
|
Sign up to set email alerts
|

3T MRI evaluation of large nerve perineural spread of head and neck cancers

Abstract: Targeted 3T MRI is highly accurate in defining the presence and extent of large nerve PNS in head and neck cancers. However, there is still a tendency to undercall the zonal extent due to microscopic, radiologically occult involvement. Superficial large nerve involvement also remains a difficult area of detection for radiologists and should be included as a 'check area' for review. Further research is required to define the role radiation-induced neuritis plays in the presence of false-positive PNS on MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 15 publications
5
64
0
Order By: Relevance
“…The presurgical accuracy and predictability of margin status has significantly improved with the use of the various targeted MRI techniques, which in most cases accurately reflect the histologic extent of the clinical PNI. 17 Similar to Baulch et al, 17 our results also show a good correlation between the radiological zonal extent and the actual histological extent of the clinical PNI. In our cohort, the targeted 3D MPRage MRI sequence demonstrated radiological evidence of clinical PNI in all cases, and is the choice of imaging modality for surgical planning at our institution.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The presurgical accuracy and predictability of margin status has significantly improved with the use of the various targeted MRI techniques, which in most cases accurately reflect the histologic extent of the clinical PNI. 17 Similar to Baulch et al, 17 our results also show a good correlation between the radiological zonal extent and the actual histological extent of the clinical PNI. In our cohort, the targeted 3D MPRage MRI sequence demonstrated radiological evidence of clinical PNI in all cases, and is the choice of imaging modality for surgical planning at our institution.…”
Section: Discussionsupporting
confidence: 90%
“…The decision to implement multimodality treatment or salvage treatment is based on the current best practice without an increase in patient morbidity and mortality. The presurgical accuracy and predictability of margin status has significantly improved with the use of the various targeted MRI techniques, which in most cases accurately reflect the histologic extent of the clinical PNI . Similar to Baulch et al, our results also show a good correlation between the radiological zonal extent and the actual histological extent of the clinical PNI.…”
Section: Discussionsupporting
confidence: 86%
“…It is also increasingly used to stage oropharyngeal (OP) cancer and detect cartilage invasion for laryngeal/ hypopharyngeal cancer. 2 MRI is also more reliable than CT at detecting the presence of pre-vertebral space invasion, 3 perineural spread 4 and retropharyngeal lymph node (LN) involvement, 5 which are all important factors for treatment decision-making. A study by Samuels et al 6 demonstrated retropharyngeal node involvement to be an independent poor prognostic feature, even for human papilloma virus (HPV)-driven OP cancer.…”
Section: Anatomical Mri Sequencesmentioning
confidence: 99%
“…PET/CT has been shown to be superior to CT alone in staging head and neck cancer, with better sensitivity for nodal disease as well as distant metastases (13). However, MRI has potential advantages over CT, including detection of perineural spread, vascular involvement, and invasion of adjacent structures, as well as better soft tissue contrast (48). In addition, diffusion-weighted MRI imaging has been investigated as a method of increasing specificity for detection of nodal metastases and may add further benefit (9).…”
Section: Introductionmentioning
confidence: 99%